Penggunaan Media Audio Visual Dalam Pembelajaran Pendidikan Agama Islam Di Sekolah Menengah Pertama Muhammadiyah 1 Gresik - Dewi, Nadiya Vidiliya Yusviya; Hasan Basri; Moh. Ahyan Yusuf Sya’bani (Jurnal Mahasiswa Pendidikan, 2022)
The learning process using developing technology is very profitable for teachers because by utilizing technology teachers can also make the learning process more fun and have a new atmosphere. The purpose of this study was to determine the use of video media as a media aid for student learning in Islamic religious education where by using video media students understand more about the material being taught and focus more on the ongoing learning process. The focus of this research is to find out (1) the use of video-based learning media in the learning process of Islamic religious education. (2) find out the obstacles in the learning process by using the media. This type of research uses descriptive qualitative research using data collection methods in the form of observation, interviews and documentation. while data analysis is done by using data reduction, data presentation and drawing conclusions. Where to find out more about the results of the research. The results of this study are that the use of video-based media in the learning process of Islamic religious education at SMP Muhammadiyah 1 Gresik goes well according to existing procedures, where use must have learning tools and media. The existence of this learning media so that students are more conducive in learning and more active in responding to learning so that students more easily understand the material being taught. As for the success of using the media itself, there are several obstacles that are felt by both teachers and students, namely in the form of inadequate facilities and pre-facilities and the length of time the learning process takes place.